2011
DOI: 10.1136/bjo.2009.169953
|View full text |Cite
|
Sign up to set email alerts
|

Expanded polytetrafluoroethylene as a substrate for retinal pigment epithelial cell growth and transplantation in age-related macular degeneration

Abstract: ePTFE can be surface-modified to support an intact functional monolayer of healthy RPE cells with normal morphology and the ability to perform RPE-specific functions. Following further investigation ePTFE may be considered for use in transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…The primary cell isolation methods, characterisation of epithelial purity and culture conditions for both cell types have been described previously [4]. ARPE-19 were used at passage 18-20; hRPE were used at passage 8-12.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The primary cell isolation methods, characterisation of epithelial purity and culture conditions for both cell types have been described previously [4]. ARPE-19 were used at passage 18-20; hRPE were used at passage 8-12.…”
Section: Cell Culturementioning
confidence: 99%
“…However, it is hydrophobic and will not allow cell attachment. Ammonia gas plasma treatment of e-PTFE has been shown to improve its hydrophilicity significantly and promote the development of a monolayer of functional RPE cells in vitro [4]. Ammonia gas plasma treatment followed by a post treatment in PBS has been shown to cause defluorination of the surface and the incorporation of oxygen-containing functionalities [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…To be able to do this it is necessary to modify the surface of the ePTFE to overcome its hydrophobicity using an ammonia gas plasma. [53] This renders the surface hydrophilic without influencing the structural or mechanical properties. We found that we could get good cell growth of primary conjunctival cells on the plasmatreated ePTFE by 14 d and that about 15% of the cells stained positive for MUC5AC although after longer time periods in vitro the total cell number reduced.…”
Section: Conjunctiva Damage and Repairmentioning
confidence: 99%
“…The rods provide trophic support to cone cells, and, consequently, healthy rod cell transplantation into RP mice lacking rods can delay cone death (8). Providing physical support, for example with the help of biopolymers, may be important for both cone viability and function (19). For end-stage retinal degeneration, in which the residual cone cells are nonfunctional or are lost, strategies such as transplanting photoreceptors (20), implanting electronic prostheses (21), or using optogenetic strategies (22) may be beneficial for restoring navigational vision.…”
Section: An "Aye" For Nrf2mentioning
confidence: 99%